2018
DOI: 10.1002/hep.29702
|View full text |Cite
|
Sign up to set email alerts
|

The RNA genome of hepatitis E virus robustly triggers an antiviral interferon response

Abstract: HEV infection elicits an active IFN-related antiviral response in vitro and in patients, triggered by the viral RNA and mediated by IFN regulatory factors 3 and 7 and the Janus kinase-signal transducer and activator of transcription cascade; these findings have revealed new insights into HEV-host interactions and provided the basis for understanding the pathogenesis and outcome of HEV infection. (Hepatology 2018;67:2096-2112).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 42 publications
4
25
0
Order By: Relevance
“…We further demonstrated that the loss of the poly(A) tail in HEV SL3 significantly reduced the IFN induction potential of SL3, although it did not completely abolish its IFN induction potential. This was in corroboration with a previous study which demonstrated the IFN induction potential by HEV full-length genomic RNA was independent of the poly(A) tail (11). A poly(A) sequence of 50 nucleotides or more in length is known to induce an IFN response via RIG-I (26).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We further demonstrated that the loss of the poly(A) tail in HEV SL3 significantly reduced the IFN induction potential of SL3, although it did not completely abolish its IFN induction potential. This was in corroboration with a previous study which demonstrated the IFN induction potential by HEV full-length genomic RNA was independent of the poly(A) tail (11). A poly(A) sequence of 50 nucleotides or more in length is known to induce an IFN response via RIG-I (26).…”
Section: Discussionsupporting
confidence: 91%
“…It was reported recently that the poly(A) tail is not essential for HEV RNA to induce the IFN response (11). Therefore, we also tested the potential of the SL3 without a poly(A) tail to induce an IFN response.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Induction of type III IFNs in HepG2 cells infected with HEV3–Kernow depend on MAVS, MDA5, and to a lesser extent RIG-I [ 56 ]. However, RIG-I, MDA5, MAVS, or β-catenin knockout cells can still produce IFN in mouse embryonic fibroblast (MEF) cells, suggesting that HEV RNA is recognized by an as-yet-unknown cytosolic RNA sensor, at least in these cells [ 57 ]. IFN induction requires IRF3 and IRF7 in this system [ 57 ].…”
Section: Hev Rna Sensing By Infected Cellsmentioning
confidence: 99%